Fantastic Elements Which Emerge Through Confusion in Children's Stories - Karakaya, Z. (Hacettepe University efdergi@hacettepe.edu.tr, 2015)
This paper deals with typical fantastic which emerges in children’s stories when children confuse stories, characters and events. Especially in pre-school period, children perceive the realities within the scope of a unique dimension since they mostly acquire concrete conception at that age. In this period, children firstly perceive concrete realities that they see and which they experience. Abstract indications, images and perceptions are progressively interiorized. These concepts are confused in the first place. In short, children may confuse the realities with their dreams and phantasies. Therefore, this paper analyzes typical fantastic elements arising from the above-mentioned confusion. This study firstly focuses on the distinction between fantastic genre and fantastic concepts, and then it gives information about the formation and emergence of typical elements. In this study, Paul Maar’s novel Lippels Traum has been analyzed as an example. In this novel, typical confusion appears especially in the inner frame of the story. The child figure in the novel confuses reality with fictional events as well as with events in his dreams. The characters, events, places and time are multi-cultural and possess universal characteristics. The narrator intervenes in transition points between the frameworks, which produces interesting instances of the fantastic. Therefore fantastic has gained individual, social and global characteristics. © 2015, Hacettepe University. All rights reserved.
Çocuk Anlatılarında Karıştırma Yoluyla Ortaya Çıkan Fantastik Unsurlar
Keywords: Confusion; Frame Story; The Fantastic; Universal Features